HOW TO LIQUIDATE AND SUSPEND THE ACTIVITIES OF NGOS: THE EXPERIENCE OF UZBEKISTAN - Bekzod Narimanov (Scholar Express Journals, 2022)
This article examines the issue of termination of the activities of NGOs and suspension of their activities in Uzbekistan in scientific, theoretical and practical terms. During the liquidation of NGOs, aspects that differ from other legal entities were studied. Practical problems in the liquidation of NGOs were analyzed and suggestions for their solution were made. Especially the problems of judicial termination of NGO activities are of a real practical nature
Keywords: Non-governmental organization; fund; liquidation commission; registration body